Immunohistochemical expression of the hepatocyte growth factor in chromophobe renal cell carcinoma - Erlmeier, Maximilian; Mikuteit, Marie; Zschäbitz, Stefanie; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; Steffens, Sandra; Erlmeier, Franziska (BMC urology, 2023)
Background: The prognostic value of Hepatocyte growth factor (HGF) in non-clear cell renal cell carcinoma (RCC) is still unclear. The aim of this study is to evaluate the prognostic impact of HGF expression in a large cohort of chromophobe RCC (chRCC). Methods: Patients who underwent renal surgery due to chRCC were recruited. Clinical data was retrospectively evaluated. Tumor specimen were analyzed for HGF expression by immunohistochemistry. Results: 81 chRCC patients were eligible for analysis, thereof 37 (45.7%) patients were positive for HGF. No significant associations were found for HGF expression and clinical attributes in patients with chRCC. Kaplan-Meier analysis revealed no differences in 5-year overall survival (OS) for patients with HGF− compared to HGF+ tumors (95.0% versus 90.9%; p = 0.410). Conclusions: In chRCC HGF expression is not associated with parameters of aggressiveness or survival.